Moving away from silence : music of the Peruvian Altiplano and the experience of urban migration - Turino, Thomas (Chicago studies in ethnomusicology., 1993)
Increasingly popular in the United States and Europe, Andean panpipe and flute music draws its vitality from the traditions of rural highland villages and of rural migrants who have settled in Andean cities. In Moving Away from Silence, Thomas Turino describes panpipe and flute traditions in the context of this rural-urban migration and the turbulent politics that have influenced Peruvian society and local identities throughout this century. Turino's ethnography is the first large-scale study to concentrate on the pervasive effects of migration on Andean people and their music. Turino uses the.